The effect of non-covalent interactions of xylitol with whey protein and casein on structure and functionality of protein. (December 2020) - Kong, Fanhua; Kang, Shimo; An, Yuejia; Li, Weixuan; Han, Hongjiao; Guan, Boyuan; Yang, Mei; Zheng, Yan; Yue, Xiqing
Abstract: The mechanisms underlying the interactions of xylitol (XY), as a functional food ingredient, with bovine whey protein isolate (WPI) and casein (Cs) were investigated via multiple spectroscopic methods, and the structural and functional changes of the proteins were explored. The interactions were evidenced by fluorescence quenching, accompanied by a blue-shift. WPI had a slightly stronger binding affinity than Cs toward XY, with respective K A values of 16.95 × 10 4  L mol −1 and 6.69 × 10 4  L mol −1 . H bonds and van der Waals forces may have significantly contributed to these interactions. Additionally, changes the environment around the corresponding amino acid residues of WPI and Cs, and decline in the α-helix structures were demonstrated by simultaneous fluorescence, three-dimensional fluorescence spectroscopy and circular dichroism, which resulted increased solubility, emulsification, and foaming, and decreased surface hydrophobicity of both the proteins. These results provide a basis for the development of a functional dairy-based product.